Public Attitudes Toward Green Energy During the Russia-Ukraine War: Social Media Sentiment Analysis - Suaad Yahya Mohammed Ali; Muhammad Kashif Majeed; Ismail Hussein Amzat (Jurnal Ilmu Sosial dan Ilmu Politik (JISIP), 2026)
The Russia-Ukraine war, beginning in February 2022, profoundly disrupted global energy markets and forced European nations to reconsider their long-standing dependence on Russian fossil fuels. This geopolitical crisis intensified public debate regarding the role of green energy in ensuring energy security and national sovereignty. This study examines public attitudes toward green energy during the first five months of the conflict through a sentiment analysis of 153,515 Facebook posts. By applying emotional intensity measurements and statistical techniques, the research identifies shifting discourse patterns across two distinct phases: Phase 1 (February–March) and Phase 2 (April–June). Findings reveal that public engagement increased substantially, with Phase 2 containing 59% more content than Phase 1. Overall sentiment shifted from slightly negative (-0.02) to positive (+0.03), characterized by a significant rise in hope and urgency alongside a marked decrease in fear. Most significantly, the framing of green energy as a tool for energy independence increased by 60%, as support grew from 21.6% to 25.9%. These results indicate that the war fundamentally reframed public discourse, positioning renewable energy as a strategic security imperative rather than a purely environmental concern. This shift presents new opportunities for accelerating energy transitions, provided that persistent concerns regarding reliability and cost are addressed.